An uncoordinated tertiary nitrogen based tricarboxylate calcium network with Lewis acid–base dual catalytic sites for cyanosilylation of aldehydes. Issue 5 (18th January 2021) - Wang, Ying-Xia; Wang, Hui-Min; Meng, Pan; Song, Dong-Xia; Hou, Juan-Juan; Zhang, Xian-Ming
Abstract : An uncoordinatedly tertiary nitrogen based tricarboxylate calcium network with Lewis acid–base dual catalytic sites have been designed and synthesized for cyanosilylation of aldehydes. Abstract : The design and utilization of dual sites for synergistic catalysts has been recognised as an efficient method towards high-efficiency catalysis in the cyanosilylation of aldehydes, which gives key intermediates for the synthesis of a number of valuable natural and pharmaceutical compounds. However, most of the reported dual-site catalysts for this reaction were homogeneous, accompanied by potential deactivation through internal complexation of the dual sites. Herein, by the rational selection of an uncoordinated tertiary nitrogen based tricarboxylic ligand (tris[(4-carboxyl)-phenylduryl]amine, H3 TCBPA), a new three-dimensional calcium-based metal–organic framework (MOF), Ca3 (TCBPA)2 (DMA)2 (H2 O)2 (1, where TCBPA = ionized tris[(4-carboxyl)-phenylduryl]amine and DMA = N, N -dimethylacetamide), possessing accessible dual catalytic sites, Lewis-basic N and Lewis-acidic Ca, has been designed and constructed by a one-pot solvothermal reaction. As expected, 1 is capable of dually and heterogeneously catalysing the cyanosilylation of aldehydes at room temperature, and can be reused for at least 6 runs with a maximum turnover number (TON) of 1301, which is superior to most reported cases. Additionally, 1 shows CO2 adsorption ability and conversion with epoxides, which is beneficial for the establishment of a sustainable society.